Haze removal for a single inland waterway image using sky segmentation and dark channel prior. Issue 12 (1st December 2016) - Liu, Wei; Chen, Xianqiao; Chu, Xiumin; Wu, Yirong; Lv, Jingwen
Abstract : Haze significantly degrades the visibility for ship navigation and traffic monitoring in China's inland waterways. In this study, the authors propose a novel haze‐removal method based on sky segmentation and dark channel prior to restore images. Sky segmentation is accomplished by using robust image matting and region growth algorithms. Then, the average image intensity of the sky region is chosen as the atmospheric light value to address the defect of dark channel prior. Experimental results show that their method can restore inland waterway images effectively; restored images are more natural and smoother than those obtained by the state‐of‐the‐art haze removal algorithms.